Non‐isothermal kinetic study of high‐grade magnesite thermal decomposition and morphological evolution of MgO. Issue 3 (13th February 2021) - Hou, Qingdong; Luo, Xudong; Li, Meiting; An, Di; Xie, Zhipeng
Abstract: Thermal decomposition was the prerequisite and basis for the utilization of magnesite resources. However, the calcination of magnesite was usually accompanied by high energy consumption, which not only caused serious waste of magnesite resources, but also restricted its high value‐added utilization. Therefore, calcination conditions were the key to controlling thermal decomposition process of magnesite. The kinetics of high‐grade magnesite thermal decomposition was elaborated by non‐isothermal thermogravimetric analysis, and meanwhile the effect of heating rate on the magnesite thermal decomposition reaction and morphology of MgO particles were characterized. Both Doyle and Gorbatchev approximate functions were used to simulate the magnesite thermal decomposition process, where the experimental data (correlation coefficient) fitted by the latter could obtain more acceptable kinetic parameters of the magnesite thermal decomposition. The good linear relationship between the activation energy and the pre‐finger factor allowed for a kinetic compensation of the thermal decomposition of magnesite. Furthermore, higher heating rate induced the formation of terraced grains, grain network group, cubic grains, and spherical grains for the samples sintered at 1200°C. The heating rate largely affected the magnesite particle morphology, grain size distribution and activity, and also provided important technical indicators in the actual production of magnesia refractory raw materials.